2022
DOI: 10.1590/1983-40632022v5271356
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic effects of Mikania micrantha Kunth on barnyardgrass and lowland rice1

Abstract: Secondary metabolites from weeds have potential as a natural herbicide and are safe for the main crop. This study aimed to screening secondary metabolites in Mikania micrantha extract and their effect on the agronomic, physiological and histological characteristics of barnyardgrass and lowland rice. A non-factorial randomized block design was used, with extract concentrations of Mikania micrantha (0; 20; 40; 60; 80; 100 %) and 2,4-D dimethyl amine herbicide as comparison. The M. micrantha extract presented fav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…mitis can lower rice grain production by 12.7 to 42.6% by inhibiting photosynthesis rate, root weight, root oxidation activity, and biomass accumulation (Zhang et al, 2017). Alridiwirsah et al (2022) added that barnyardgrass had five populations in lowland rice, with root length and volume of 39.4cm and 246.1ml and dry weight of roots and shoots of 92.7 g and 65.6g, respectively.…”
Section: Methodology and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…mitis can lower rice grain production by 12.7 to 42.6% by inhibiting photosynthesis rate, root weight, root oxidation activity, and biomass accumulation (Zhang et al, 2017). Alridiwirsah et al (2022) added that barnyardgrass had five populations in lowland rice, with root length and volume of 39.4cm and 246.1ml and dry weight of roots and shoots of 92.7 g and 65.6g, respectively.…”
Section: Methodology and Data Analysismentioning
confidence: 99%
“…According to Tahir (2016), the barnyardgrass from several locations in Arkansas has a leaf length of 16.2 to 30.0cm, a leaf width of 1.2-1.5 cm, upper glume of 2.94 to 3.80mm, lower glume of 1.21 to 1.68mm, an upper lemma of 2.71 to 3.55mm, and 7,186-71,494 seeds per plants. Alridiwirsah et al (2022) also added that the upper epidermis, mesophyll, lower epidermis, and stomata density of barnyardgrass leaves from lowland rice plants were 44.3 μm, 155.6μm, 40.8μm, and 69.0n/μm, respectively.…”
Section: Methodology and Data Analysismentioning
confidence: 99%
“…M. micrantha is rich in terpenoids, phenolics, flavonoids, alkaloids, tannins, saponins, glycosides, and steroids [51,52]. The literature consistently show that natural ACE inhibitors can be found in plant secondary metabolites containing terpenoids, phenolic, flavonoids, hydrolysable tannins, xanthones, procyanidins, and caffeolyquinic acid derivatives [44].…”
Section: Angiotensin-i Converting Enzyme (Ace) Inhibition Activitymentioning
confidence: 99%
“…Plants, including weeds, produce allelochemicals that defend against pests, diseases, and competition from other plants (Kong et al, 2019). In addition, Alridiwirsah et al (2022) found that Mikania micranta extract had alkaloids, flavonoids, saponin, and tannins as well as an extract concentration of 20-100%, which effectively suppressed the biomass of barnyard grass weeds by 46.0-63.5% in lowland rice area. Weeds that exist in swampland are not widely known for their compund content.…”
Section: Introductionmentioning
confidence: 99%